Results of surgical treatment of cervical cancer patients of childbearing age - V. S. Navruzova (ABV-press, 2015)
The world marked increase in the incidence of cervical cancer in young women, especially from 29 to 45 years old. Analysis showed that in patients with preserved ovarian function, not only the effectiveness of the treatment, but also the quality of life. It is associated with the acceleration, earlier puberty and the onset of sexual activity. In recent years more and more widely used radical surgery with preservation of the ovaries and the abduction of the radiation castration and preservation of reproductive function. In the National Cancer Research Centre of the Ministry of Health of the Republic of Uzbekistan analyzed the results of surgical treatment of 204 patients with cervical cancer younger. Age of patients from 23 to 45 years, that is, in the most hard-working, reproductive period. In our study patients met principally with exophytic - 82 (40.2 %) and 68 (33.3 %) еndophytic growth cervical tumors. Histological in 197 (96.6 %) patients with squamous cervical cancer patients with 7 (3.4%). Adenocarcinoma of cervical cancer. Handard examination of the patient are further adapted to determine the level of sex hormones (estradiol, progesterone), determination of the tumor marter CA-125 levels of calcium and phosphate in the blood. 112 patients from the main group and the combined complex therapy surgical treatment with organ-component (conservation and ovarian transposition). The first group included 112 (55.1 %) patients, who as part of combination therapy was performed and complex surgical treatment of ovarian transposition. The second group included 92 (44.9%) patients who as part of combination therapy and complex surgery performed without ovarian transposition. Each group was divided into 3 subgroup included patients with stage process T1b-2aN0M0. Which performs the combined radiotherapy. The second subgroups included patients with stage process that runs systemic chemotherapy, surgery, combined radiotherapy. The third group included patients with stage process that runs endoarterial regional prolonged chemotherapy + surgery + combined radiotherapy. In phases of dynamic monitoring of patient evaluated the effectiveness of treatment as well as studied T2bN0-1M0 the quality of life of a young body. Quality of life of patient in the dynamics of observation was determined by the American system MENQOL.